ANALISIS KEBERLANJUTAN AGRIBISNIS PADI SAWAH DI DESA ALLITA, KECAMATAN MATTIRO BULU, KABUPATEN PINRANG, PROVINSI SULAWESI SELATAN - Nurhapsa, Nurhapsa; St. Rohani, St. Rohani; Rasyid, Ilham; Sirajuddin, Siti Nurani; Mukhlis, Mukhlis (Program Studi Agribisnis Fakultas Pertanian, 2025)
Agriculture is a very important sector in human life, providing food and raw materials for various industries. However, along with the increasing demand for food due to global population growth, conventional agricultural practices have faced various serious challenges that threaten environmental sustainability and the welfare of farmers. The concept of sustainability in agricultural businesses emerged as a solution to overcome these challenges. Agricultural sustainability emphasizes practices that can maintain a balance between economic, environmental, and social needs. This research aims to analyze the level of sustainability of lowland rice businesses using a composite index from Likert scale data on farmers' perceptions. The research was conducted in Alitta Village, Mattiro Bulu District, Pinrang Regency, in May 2024. The analysis used in this research was measured by creating a composite index of sustainability efforts. The research results show that the sustainability index for lowland rice businesses in Alitta Village is assessed from two dimensions: economic and social. In the economic dimension, most variables are in the medium sustainability index category. Meanwhile, the variables for the incidence of crop failure and the sufficiency of family needs are in the low sustainability index category. Meanwhile, in the social dimension, the variables of knowledge about farming methods and level of motivation are in the high sustainability index category. Meanwhile, the variables for labor absorption and family involvement in farming are in the medium and low sustainability index categories.